Analysing Support towards Inclusive and Integrated Rural Advisory Systems - Julien Lamontagne-Godwin; Peter Dorward; Naeem Aslam; Sarah Cardey (Social Sciences, 2019)
Public Rural Advisory Services (RAS) have adapted to different socio-economic scenarios in politically diverse countries with the help of the third sector supporting dedicated RAS programmes. The Plantwise (PW) programme, led by the Centre for Agriculture and Bioscience International (CABI) and designed to increase food security in over 30 countries, is a good example of a public/NGO partnership, although recent evaluations have questioned its impacts on gendered agricultural information access. This study aims to investigate Plantwise’s gender impacts from individual and institutional viewpoints, interviewing smallholder farmers and extension staff involved in and outside of, the Plantwise programme in Bahawalpur and Jhang district in the Punjab province of Pakistan. This serves to highlight the programme’s impacts on systemic processes which ultimately have the potential to contribute to gender-transformative change and a more efficient and sustainable RAS. Results show differences between extension workers in a PW district and a non-PW district and between plant doctors and non-plant doctors in a PW district, though none were significant from a gendered perspective. There were interesting findings highlighting the plant clinic’s capacity as an agent of change but the low turnout of women at clinics did not reinforce the clinics’ capacity for change from a female perspective. Information from systemic, male and female-specific analyses are important to consider for PW from a practical perspective, such as the importance of spiritual locations. This study into the Pakistani PW initiative also offers an opportunity to contribute to the growing body of academic literature on the individual and institutional impacts of international development programmes, helping to understand wider aspects of international development involvement in RAS. From a practical perspective, this study also enables PW and other international development initiatives to better understand and interpret stakeholders’ perceptions, highlighting the importance of design and investment in participatory approaches to enable longer term impacts, especially focused on gender. It will also help the PW programme assess and understand implementation challenges in order to attain impact on the ground and be a driver of positive change in the country.